2013
DOI: 10.1177/000348941312200106
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Respiratory Epithelium Regeneration from Induced Pluripotent Stem Cells

Abstract: This study demonstrated the potential use of iPS cells in regeneration of the respiratory epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…10 In previous histological experiments, we confirmed that iPSCs have the potential to differentiate into respiratory epithelium-like tissue. 11 Respiratory epithelium-like tissue was observed in EBs by culturing in serum-free differentiation medium supplemented with activin A and bFGF. However, their differentiation into ciliated cells could not be confirmed immunohistologically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In previous histological experiments, we confirmed that iPSCs have the potential to differentiate into respiratory epithelium-like tissue. 11 Respiratory epithelium-like tissue was observed in EBs by culturing in serum-free differentiation medium supplemented with activin A and bFGF. However, their differentiation into ciliated cells could not be confirmed immunohistologically.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous experiments confirmed that iPSCs have the potential to differentiate into respiratory epithelium-like tissue, as shown by immunohistochemical examination. 11 As cytokeratin AE1/3 is a specific marker of basal cells, antibodies against cytokeratin AE1/3 were used to identify differentiated cells. Basal cells stained with the antibodies were observed on the basement membrane of the epithelium.…”
Section: Immunohistochemical Analysismentioning
confidence: 99%
“…A controversial multipotent lung stem cell has also been claimed to exist (35). Exogenous sources of stem cells that have been proposed for use include bone marrow-derived nonhaematopoietic or mesenchymal stem cells (41)(42)(43), embryonic stem cells (ESCs) (44)(45)(46)(47), human amniotic fluid-derived stem cells (48) and induced pluripotent stem cells (49). Endogenous mesenchymal progenitors include fibroblast growth factor 10-releasing mesenchymal cells (reported in (50)), but knowledge of these cells is limited and the literature is focused on airway epithelial progenitors at present.…”
Section: Stem Cell Populations Of the Airwaysmentioning
confidence: 99%
“…The ramifications of this paper could be revolutionary, not only for respiratory tissue engineering and regeneration but also for stem cell biology, as a multipotent cell capable of differentiating down two different germ lineages has never been discovered. As such, this work has been met with some consternation over the choice of controls, lack of lineage tracing and the choice of cellular markers (63) (48,49). iPSCs were recently developed by transduction of 4 transcription factors and show great promise as a tool for tissue regeneration and as a means of creating disease-specific drug development tools (64,65).…”
Section: Other Lung Stem Cell Populationsmentioning
confidence: 99%
“…Chondrocytes have limited proliferation capacity and rapidly lose their differentiated phenotype in culture 17 . Therefore, chondrogenic cells derived from induced pluripotent stem cells (iPSCs) have emerged as a promising source to enhance cartilage regeneration [18][19][20] . The most significant benefit of iPSC-derived progenitor cells for cartilage regeneration is that they may provide an unlimited supply of chondrogenic cells for in vivo applications.…”
mentioning
confidence: 99%